Work procrastination and work-life balance as predictors of employee performance: evidence from a state-owned logistics company in Surabaya - Alyyah Rahma Putri Hani; Dewi Khrisna Sawitri (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Sustaining employee performance has become a strategic priority for organizations operating in highly demanding and competitive environments. Over the past three years, a state-owned logistics organization in Surabaya has experienced a consistent decline in employee productivity, underscoring the need to identify key behavioral and organizational factors influencing performance outcomes. This study examines the effects of work procrastination and work–life balance on employee performance within the organization. Adopting a quantitative research design and a census sampling approach, the study involved all 112 employees as respondents. Data were collected through structured questionnaires employing a five-point Likert scale and supported by semi-structured interviews and direct field observations. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that work procrastination has a significant negative effect on employee performance, indicating that delays in task completion adversely affect productivity and work outcomes. Conversely, work–life balance positively and significantly influences employee performance, suggesting that employees who achieve a better balance between professional and personal responsibilities are more likely to perform effectively. Collectively, both variables explain 65.4% of the variance in employee performance, demonstrating substantial predictive power. The study contributes to the organizational behavior and human resource management literature by highlighting the dual importance of minimizing counterproductive work behaviors and fostering employee well-being to enhance performance. These findings offer practical implications for managers in state-owned enterprises seeking to improve organizational effectiveness through targeted interventions that reduce workplace procrastination and promote work–life balance initiatives. Keywords: Employee Performance; Work Procrastination; Work-Life Balance